FRI0503 Validation of new potential targets for remission in psoriatic arthritis in patients treated with golimumab. (15th June 2017) - Coates, LC; Rahman, P; Psaradellis, E; Karellis, A; Rampakakis, E; Osborne, B; Tkaczyk, C; Lehman, AJ; Nantel, F
Abstract : Background: Treat to target recommendations in psoriatic arthritis (PsA) stated that the target of treatment should be remission or inactive disease. At that time, no definitions of remission or inactive disease existed and the only validated target available was the minimal disease activity (MDA) criteria. Since then, other potential targets have been developed including very low disease activity (VLDA) and the Disease Activity in PsA (DAPSA) score remission. Objectives: Using an existing dataset allowing calculation of DAPSA and clinical cDAPSA scores and the VLDA criteria, the objectives were to calculate the proportion of patients achieving these criteria, their prognostic value and the overall patient impact of these disease states. Methods: BioTRAC is an ongoing, prospective registry of inflammatory arthritis patients initiating treatment with infliximab, golimumab (GLM) or ustekinumab. PsA patients treated with GLM were included. Data collected at baseline, 6 and 12 months (mts) were used. DAPSA remission was defined as: TJC + SJC + PtGA + Pt pain + CRP ≤4. cDAPSA Remission was defined as: TJC + SJC + PtGA+ Pt pain ≤4. Very low disease activity (VLDA) was achieved when all 7 MDA criteria were satisfied: TJC28≤1, SJC28≤1, PASI≤1, Pain (VAS) ≤15mm, PtGA (VAS) ≤20mm, HAQ ≤0.5 and tender entheseal points ≤1. Correlation between DAPSA, cDAPSA and VLDA were based on tetrachoric analysis. Results: A total of 188 patients (53.2% female gender) were included with a mean (SD) disease duration of 5.46 (6.91) years. DAPSA remission was achieved in 5.1%, 24.2% and 30.0% of patients at baseline, 6 mts and 12 mts, respectively. Those patients had a significant reduction in the number of TJC, SJC, enthesitis and dactylitis (p<0.043). cDAPSA remission was achieved in 5.2%, 33.1% and 38.3% of patients at baseline, 6 mts and 12 mts, respectively. Those patients had a significant reduction in the number of TJC, SJC and enthesitis only (p<0.002). VLDA was achieved in 2.1%, 17.2% and 15.6% of patients at baseline, 6 mts and 12 mts, respectively and those patients had a significant reduction in the number of TJC, SJC, enthesitis and PASI (p<0.002). The overall correlation for DAPSA or cDAPSA remission vs. VLDA achievement were both at 0.999 (Asymptotic Standard Error <0.027) although this is likely driven by the high number of patients who are not in either state. 75% and 53.3% of patients in DAPSA and cDAPSA remission, respectively, also achieved VLDA (p<0.001). In contrast, patients who did not achieve neither cDAPSA nor DAPSA never achieved VLDA. Nonetheless, patients in remission had significantly greater HAQ scores (p<0.03) if they had remaining dactylitis or active skin disease (BSA≤10%; cDAPSA only). Conclusions: DAPSA, cDAPSA and VLDA represent new potential target for remission in PsA with VLDA being the most stringent criteria. There was a high level of correlation between these scores although residual activity in dactylitis and skin despite DAPSA remission has some impact on patients' function. Disclosure of Interest: L. Coates Grant/research support from: Abbvie, BMS, Celgene, Janssen, Lilly, MSD, Novartis, Pfizer, Sun Pharma, UCB, Consultant for: Abbvie, BMS, Celgene, Janssen, Lilly, MSD, Novartis, Pfizer, Sun Pharma, UCB, P. Rahman Consultant for: Abbott, AbbVie, Amgen, BMS, Celgene, Janssen, Novartis, Pfizer, Roche, E. Psaradellis Employee of: JSS Medical Research, A. Karellis Employee of: JSS Medical Research, E. Rampakakis Employee of: JSS Medical Research, B. Osborne Employee of: Janssen, C. Tkaczyk Employee of: Janssen, A. Lehman Employee of: Janssen, F. Nantel Shareholder of: Jonhson and Johnson, Employee of: Janssen